Recent Publications (Quarterly Journal of Economics, 1940)
Journal Article Recent Publications Get access The Quarterly Journal of Economics, Volume 54, Issue 3, May 1940, Pages 535–537, https://doi.org/10.1093/qje/54.3.535 Published: 01 May 1940